Tingkat Kejadian Kecacingan Sapi Potong pada Peternakan Rakyat di Kabupaten Mesuji - A Setiawan; A A Candra; Z Zairiful (Politeknik Negeri Lampung, 2022)
Incidence rate of helminthiasis in Mesuji District is not yet known, the importance of basic data on helminthiasis cases to help farmers who are developing beef cattle farming businesses so as not to cause a decrease in economic value. Research held in beef cattle smallholder farms at Mesuji District on December 2021 – January 2022. This study aims to analyze the Incidence rate of helminthiasis cases. The research type is exploration method. Data collection was done by taking all fecal sample from 360 beef cattle in Way Serdang sub-district and Simpang Pematang sub-district. Fecal samples examination checked with Mc. Master and Sedimentation test at Veterinary Laboratory of Lampung. The results showed that the percentage of helminthiasis Incidence rate in Mesuji District was 66,7%, there were worms of the Nematode 41,6%, Trematode 73,8% and Cestode 1,94% classes. The highest incidence rate of helminthiasis in beef cattle at smallholder farms in Mesuji district ranging from 100-1.500 eggs